2019
DOI: 10.1002/chem.201901673
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Variability of [Ge9] Cluster Chemistry through Phosphine Functionalization

Abstract: The synthetic approach towards molecules that contain Ge atoms with oxidations tate 0, and which are exclusively connected to other Ge atoms, is explored by using anionic clusters extracted from binary solids. Besides providing an ovel variable method for the introductiono fa lkenyl moieties to [Ge 9 ]c lusterc ompounds, this work expands the spectrum of mixed-functionalized [Ge 9 ]c luster anions, which are suitable for the straightforward synthesis of zwitterionic compounds upon coordination to metal cations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 76 publications
0
17
0
2
Order By: Relevance
“…Thus, mixed substituted clusters featuring various group 14 element fragments became accessible. [36][37][38][39][40][41] However, the attachment of phosphanyl-moieties [42][43][44][45] to [Ge 9 ] showed that the clusters can be decorated with more interesting Lewis basic functional groups. Similarly of interest is the addition of a ligand comprising an electron-decient boranyl moiety by our group.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mixed substituted clusters featuring various group 14 element fragments became accessible. [36][37][38][39][40][41] However, the attachment of phosphanyl-moieties [42][43][44][45] to [Ge 9 ] showed that the clusters can be decorated with more interesting Lewis basic functional groups. Similarly of interest is the addition of a ligand comprising an electron-decient boranyl moiety by our group.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the shielding of the [Ge 9 ] core, reactions of the tris‐silylated cluster are limited to the introduction of less bulky main group element ligands, yielding uncharged cluster compounds with Ge−C, Ge−P and Ge−Sn exo ‐cluster bonds such as [Ge 9 {Si(TMS) 3 } 3 R] [R: Et, [8] (CO) t Bu, [9] t Bu, [9] {(CH 2 ) n CH=CH 2 } ( n : 1, 3) [7c] ], [Ge 9 {Si(TMS) 3 } 3 (PRR l )] (R=R l : i Pr, Cy; [5] R: t Bu, R l : {(CH 2 ) 3 CH=CH 2 } [10] ), and [Ge 9 {Si(TMS) 3 } 3 SnR 3 ] (R: n Bu, [8] Ph [11] ). Except for the Sn‐containing species, which (partially) show multicenter Ge−Sn bonds, all main group element fragments are attached to the [Ge 9 ] entity via 2‐center‐2‐electron (2c‐2e) bonds pointing radially away from the center of the cluster.…”
Section: Methodsmentioning
confidence: 99%
“…Using a rigid bis-halo-silane, a connection of two clusters to the anion [{Si(SiMe 3 ) 3 } 2 Ge 9 -SiMe 2 -(C 6 H 4 )-SiMe 2 -Ge 9 {Si(SiMe 3 ) 3 } 2 ] 2À is achieved. [17] Comparable to the reactions reported for the tris-silylated species, alkyl-, germanylor phosphanyl-decorated anions [Ge 9 {Si(TMS) 3 }Et] 2À (one Si(TMS) 3 group is cleaved upon crystallization), [18] [Ge 9 {Si-(TMS) 3 } 2 Ge(TMS) 3 ] À [19] or [Ge 9 {Si(TMS) 3 } 2 (PRR l )] À (R, R l : alkyl, aryl, aminoalkyl) [5,10,20] can be synthesized, revealing the prosperous chemistry of [Ge 9 {Si(TMS) 3 } 2 ] 2À with halomain group element compounds.…”
mentioning
confidence: 99%
See 2 more Smart Citations